Super-ultralow temperature laser cooling via interacting dark-state resonances - Moeini, Vase; Seyedeh Hamideh Kazemi; Mahmoudi, Mohammad (arXiv.org, 2018)
We propose a laser cooling mechanism that leads to a temperature significantly lower than the single-photon recoil limit, about \(4× 10^{-4}\,E_{r}\). This mechanism benefits from sharp and high-contrast spectra which are induced by interacting dark-state resonances. It is theoretically demonstrated that four-level atoms illuminated by two counter-propagating probe beams and two additional beams directed perpendicularly to other two, exhibit new cooling effects; For red detuned probe lasers, atoms can be subject to a strong viscous force with an extremely small diffusion, characteristic of heating caused by the stochastic nature of spontaneous emission processes. By quantum mechanical simulations, we then find that the lowest temperature approaches 0.3 nK for the case of mercury, significantly lower than the recoil energy limit. A further advantage of our proposed scheme is that there is no need for an external magnetic field or a strong external confining potential.